Synthesis of Amphiphilic Comb‐Shape Copolymers Via Ring‐Opening Polymerization of a Macromonomer. Issue 16 (14th July 2015) - Zhang, Xiaojin; Zhang, Zhenguo; Su, Xin; Dong, Hui; Zhong, Zhenlin; Zhuo, Renxi
<x xml:space="preserve">Abstract</x> Amphiphilic comb‐shape copolymers PCL‐co‐P(MTC‐mPEG16) (where PCL, MTC, and mPEG refer to poly(ε‐caprolactone), 2‐methyltrimethylene carbonate, and methoxy poly(ethylene glycol), respectively) are synthesized by ring‐opening polymerization of ε‐caprolactone and cyclic carbonate‐terminated PEG macromonomer (MTC‐mPEG16) with benzyl alcohol as an initiator and Sn(Oct)2 as a catalyst. Amphiphilic copolymers PCL‐co‐P(MTC‐mPEG16) can form micelles in aqueous solution by self‐assembly. The diameters of PCL‐co‐P(MTC‐mPEG16) micelles characterized by dynamic light scattering area few dozens of nanometers with a narrow size distribution and the morphology of the micelles observed through transmission electron microscopy are nanosized spheres. The in vitro drug release of comb‐shape copolymer PCL‐co‐P(MTC‐mPEG16) micelles is more stable and sustained than that of linear block copolymers mPEG‐b‐PCL.